Co-opetition between local companies and subsidiaries of MNEs in Vietnam - Trinh, Viet (fi=Turun yliopisto|en=University of Turku|, 2017)
Co-opetition is an emerging facet of global business. It has gained increasing attention in academic literature. This study discusses motives of co-opetition between subsidiaries of multinational enterprises (MNEs) and local companies. The purpose of this study is to suggest a framework, which delineates the motives of local companies and MNEs when getting involved in co-opetitive relationships. The thesis elaborates answers to the main research question: “What factors drive co-opetition between local companies and subsidiaries of MNEs. Due to an underdeveloped literature on co-opetitive relationships between local companies and subsidiaries of MNEs, the study’s literature review firstly includes theoretical discussions relating to motives of MNEs and SMEs separately. It then synthesizes different theoretical perspectives in order to create a conceptual framework. Methodologically, a qualitative approach is selected, using case studies, in order to empirically develop the theoretical framework and compare the findings with the current literature on motives for co-opetition. Two cases belonging to two different industries in the Vietnamese economy were chosen. Empirical data was collected through semi-structured interviews. The key respondents in this research were employees at managerial level of the case companies. The findings of this research reveal important motives leading to co-opetition from the perspective of both, the local companies and the subsidiaries of MNEs. In terms of MNEs’ subsidiaries, two crucial motives relate to the improvement of local linkages and the increase in strategic flexibility. Concerning local companies, three essential motives are to facilitate internationalization processes, to overcome challenges related to liabilities of smallness and newness, and to improve social legitimacy and reputation. In addition it was found that resources, capabilities and innovation activities were required to help firms achieve their intended outcomes. This research provides fundamental knowledge about motives for co-opetition between local companies and subsidiaries of MNEs. Future research should conduct more empirical studies in order to develop our knowledge about co-opetition motives and capabilities needed in this context. For instance, what are the sources and means for local companies to find and develop international opportunities through co opetition? What are factors affecting success of a co-opetition strategy?